p16 Influence on Laryngeal Squamous Cell Carcinoma Relapse and Survival - Sánchez Barrueco, Álvaro; González Galán, Fernando; Villacampa Auba, José Miguel; Díaz Tapia, Gonzalo; Fernández Hernández, Sofía; Martín-Arriscado Arroba, Cristina; Almodóvar Álvarez, Carlos (My University, 2019)
Objective. (1) To identify p16 protein in laryngeal squamous cell carcinoma (LSCC) specimens and to correlate it with the presence of human papillomavirus (HPV) found in these specimens from a previous study. (2) To analyze p16 impact on 10-year overall and disease-free survival. Study Design. Retrospective case series with oncologic data base chart review. Setting. Academic tertiary care hospital. Subjects. A total of 123 samples of LSCC (taken from the glottis only) from patients treated with primary surgical resection between 1977 and 2005. Methods. p16 protein expression was analyzed through immunohistochemistry and compared with the presence of HPV established in our previous studies. Results were com pared with histologic, clinicopathologic, and survival para meters, with a 10-year follow-up. Results. Of the samples, 39.02% were positive for p16, but only 11.38% were positive for both p16 and HPV. The p161 cohort showed a significant improvement in disease-free survival (P = .0022); statistical significance was not achieved for overall survival. p161 cases had fewer relapses over time, with no relapses after a 2-year follow-up. Age at the time of diagnosis and tobacco consumption were the only epidemiologic factors that influenced overall survival. Conclusion. The expression of p16 protein was a beneficial prognostic factor for disease-free survival among patients with LSCC of the glottis, with no relapses after a 2-year follow-up